Gestão do conhecimento e rede colaborativa: modelo conceitual e representação do conhecimento em unidade de conservação de uso sustentável - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Sustainable Use Conservation Units (UCS) are areas established by the public power in order to conserve the environment. They should associate nature conservation with the controlled use of natural resources. In the UCS this scenario allowed for specific arrangements of institutions to create a community-based forest enterprise (CFE) with the objective of managing these resources in a sustainable way, and by doing so, providing income for the tradicional populations. The major challenge was to promote timber production through community forest management (CFM), without destroying the forest. The experience of the CFM directly contributed to the formation of a stock of knowledge, which presented itself as informal and not organised, making difficult to use it efficiently. In this context, the main objective of the thesis is to elaborate a conceptual model representing a semantic framework of reference in order to formally represent the knowledge in the UCS allowing the actors of the collaborative network to share it unambiguously. In order to do that, this work sought to identify the main components of the model and its attributes before instantiating them into the contextual reality of the CFM and finally to design a semantic framework. This is a research study taking a qualitative theoretical-empirical approach with the use of a computational tool to create na Ontology based on the CFM scenario in UCS. By designing and building a knowledge base, the Onto-ForestManagement ontology proved to be relevant as the first step towards deploying Knowledge Management in UCS because of its breadth and rich vocabulary of about CFM knowledge. The Ontology brings relevant elements for the description and understanding including the presentation of two taxonomies namely a taxonomy of concepts with thirty-two classes which were mapped from the point of view of specialists and a taxonomy of relations with nineteen properties of objects. Its validation was established by the criteria of coherence, clarity and objectivity and compliance to the ontological commitment, which allowed to meet the requirements and planned purposes as a potential opportunity to disseminate knowledge among stakeholders as well as serve as basis of future project focused on development of new systems.
Keywords: Gestão do conhecimento; Colaboração; Unidade de conservação de uso sustentável; Ontologia; Referencial semântico; CNPQ::CIÊNCIAS SOCIAIS APLICADAS; GESTÃO DO CONHECIMENTO E INOVAÇÃO TECNOLÓGICA PARA O DESENVOLVIMENTO SUSTENTÁVEL